2020
DOI: 10.1016/j.mce.2020.110741
|View full text |Cite
|
Sign up to set email alerts
|

The tissue-specific effects of different 17β-estradiol doses reveal the key sensitizing role of AF1 domain in ERα activity

Abstract: 17β-Estradiol (E2) action can be mediated by the full-length estrogen receptor alpha (ERα66), but also by the AF1 domain-deficient ERα (ERα46) isoform, but their respective sensitivity to E2 is essentially unknown. To this aim, we first performed a dose response study using subcutaneous home-made pellets mimicking either metestrus, proestrus or a pharmacological doses of E2, which resulted in plasma concentrations around 3, 30 and 600 pM, respectively. Analysis of the uterus, vagina and bone after chronic expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Nonetheless, it is well known that in vitro the concentration-dependent effects of E2 on both ERα-triggered ERE-based gene transcription and cell proliferation usually follow a bell-shaped curve with low-and supra-physiological concentrations of E2 (i.e., pM and µM, respectively) having the same effects. Remarkably, these observations have been also confirmed in animal models where different tissues are differentially sensitive to low or high levels of E2 [37].…”
Section: Relationships Between E2 Concentrations and E2:erα Signaling To Cell Proliferationmentioning
confidence: 57%
See 3 more Smart Citations
“…Nonetheless, it is well known that in vitro the concentration-dependent effects of E2 on both ERα-triggered ERE-based gene transcription and cell proliferation usually follow a bell-shaped curve with low-and supra-physiological concentrations of E2 (i.e., pM and µM, respectively) having the same effects. Remarkably, these observations have been also confirmed in animal models where different tissues are differentially sensitive to low or high levels of E2 [37].…”
Section: Relationships Between E2 Concentrations and E2:erα Signaling To Cell Proliferationmentioning
confidence: 57%
“…In addition, in this case, the regulation of DNA synthesis induced by different E2 concentrations has not been thoroughly investigated. Recent evidence in mice shows that supraphysiological concentrations of E2 inhibit uterine epithelial cell proliferation and, consequently, the E2-induced increase of uterine weight [37]. In ERα overexpressing cells, E2-induced DNA synthesis occurs as rapid as 6 h [44,45].…”
Section: Relationships Between E2 Concentrations and E2:erα Signaling To Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…14 Specific 17β-estradiol (E2) effects are dose-dependent and differ between tissues. 15 Additionally, several studies have found that the effect of estrogen varies based on dosing kinetics both in vitro 16; 17 and in vivo . 18 Typically, estrogen exerts its effects on cells by activating the nuclear estrogen receptors alpha and beta, which then regulate transcription of many genes.…”
Section: Introductionmentioning
confidence: 99%